2010
DOI: 10.1016/s1684-1182(10)60031-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extended-spectrum β-lactamase-producing Escherichia coli and Klebsiella pneumoniae on the Outcome of Community-onset Bacteremic Urinary Tract Infections

Abstract: Male gender and healthcare facility residency are risk factors for ESBL-producer infections among patients with community-onset bacteremic UTIs. Patients with bacteremic UTIs caused by ESBL-EK also have prolonged hospital stays and higher antibiotic costs. Early detection of ESBLs and appropriate antibiotic coverage are likely to shorten hospital stays and reduce medical costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 16 publications
3
39
1
2
Order By: Relevance
“…Whether there is a survival difference in patients with good predicted prognosis (BSIMRS of Ͻ5) at initial presentation remains unclear. This may explain the lack of significant difference in mortality among patients with BSI who received appropriate and inappropriate empirical antimicrobial agents in prior studies, particularly when the majority of included patients had a urinary source of infection (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Whether there is a survival difference in patients with good predicted prognosis (BSIMRS of Ͻ5) at initial presentation remains unclear. This may explain the lack of significant difference in mortality among patients with BSI who received appropriate and inappropriate empirical antimicrobial agents in prior studies, particularly when the majority of included patients had a urinary source of infection (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of resistance to commonly used antibiotics have often been recorded among this group of bacteria worldwide [7,8]. In the last two decades, outbreaks of infections caused by extended-spectrum blactamase (ESBL)-producing Enterobacteriaceae have largely been reported [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, while several authors reported that age >65 years was predictor for ESBL infection, 13,14 others have not confirmed this. [15][16][17] In our study, 62% of patients were >60 years. Accordingly, age was not a risk factor, which could presumably be due to the selection bias.…”
Section: Discussionmentioning
confidence: 51%